Pelayanan Non Terapeutik Program Bimbingan dan Konseling di Sekolah Indonesia Kuala Lumpur - Winingsih, Evi; Nursalim , Mochamad; Titin Indah Pratiwi; Habsy, Bakhrudin Ali (Abimanyu : Jornal of Community Engagement, 2025)
Based on the situation analysis, there are various limitations to guidance and counseling teacher services as well as support from study teachers in implementing guidance and counseling services. In 2023 SIKL will try to implement an independent curriculum. This is one of the limitations of guidance and counseling services in developing independent curriculum-based guidance and counseling services. This then encouraged developers to collaborate with guidance and counseling teachers and study teachers at the Kuala Lumpur Indonesian School. This activity will be aimed at all Guidance and Study Teachers at the school. This training activity was carried out face to face twice and had a time lag. This is done because we implement an on class and off class system. In off class activities, students are given assignments independently via their Google Classroom account. The output resulting from this research is an increase in the soft skills of guidance and counseling teachers and subject teachers in comprehensive guidance and counseling services. Apart from that, other outputs from this activity are PKM articles, articles published in the mass media and also videos distributed via the YouTube channel. Keywords: guidance and counseling training, non-therapeutic, basic services